The Sport-Culture Conflict and Its Resolution in the Media Perspective - Fangni Li (Journal of Linguistics and Communication Studies, 2023)
The increased interconnectedness of the world, combined with the advancements in technology, has raised people’s expectations of the world around them. Sports culture is certainly a noteworthy part of the social landscape; It has become a fundamental element of the contemporary human experience. Although economics and politics can have a profound impact on sports culture, the manner in which it is expressed varies greatly from country to country and region to region. This has impeded collaboration and exchange between nations in the sporting arena, resulting in unwanted tension and disputes. Hence, addressing and tackling these predicaments is of utmost importance and should be done without delay. This paper employs a variety of research techniques to delve into the issue of sport-cultural clashes and arrive at a practical and feasible solution to either reduce or avert them, as perceived by the media.